24-Hour Measurement of Gastric pH in Rural South Africa. (12th March 2015) - Sammon, Alastair M.; Ndebia, Eugene J.; Umapathy, Ekambaram; Iputo, Jehu E.
Abstract : Background . Previous studies have established norms of 24-hour gastric pH profiles for western countries. This study was designed to establish the pattern for a rural African population with a high incidence of oesophageal cancer. Methods . After lower oesophageal manometry a probe was placed 10 cm distal to the lower oesophageal sphincter. We carried out 24-hour ambulatory monitoring of gastric pH on 59 healthy subjects. This was satisfactorily completed on 26 female and 18 male (age 21–64, median 35) subjects in the Transkei region of South Africa. Results . The mean 24 hour gastric pH was 2.84 and the mean night-time pH was 3.7. 40 volunteers recorded a night-time pH reaching over 4. 33 volunteers recorded a night-time pH over 7. Night-time alkalinisation was present for 136.4 minutes (25th centile 22.8, 75th centile 208.1) at pH4 or over, and 79.3 (2.5, 122.7) minutes at pH7 or over. Episodes of rapid alkaline rise were 17 (10, 47). 21.1% of these occurred while supine. 35 of 36 tested subjects were positive for H. pylori IgG. Conclusion . Gastric alkalinisation is common in Transkei, at a higher pH than that reported in other studies, and is sustained longer. Nighttime alkalinisation is frequent. This suggests a high level of duodenogastric reflux.